Budaya Demokrasi Masyarakat Sipil Manggarai di Media Sosial - Ferdinandus Jehalut; Nyarwi Ahmad (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2024)
This article explains the democratic culture of civil society of Manggarai on social media based on a case study in the Facebook group Manggarai Bebas Berpendapat. Data were collected through observation, in-depth interviews, and documentation. The result shows that political participation in the group is manifested in the form of information provision, discursive deliberation and contestation, and efforts to influence public policy. Discursive deliberation and contestation appear in the form of user-generated framing wars, symbolic discursive deliberation and contestation, and sentimentality. In general, the democratic culture of Manggarai civil society on social media is dominated by a posttruth democratic culture.